Өндөр температурын хэт дамжуулагч YBa_2Cu_3O_7,8 керамикийн хувийн эсэргүүцэл-температурын хамаарал - Н, Содном; С, Доржханд; М, Цэрэнчимэд; Ч, Гантулга (Scientific transaction of the National University of Mongolia. Physics, 2022)
The temperature dependence of electrical resistivity of High Temperature Superconductivity of YBa2Cu307 ceramics is investigated over an interval between 95 K and 300 K on three specimens with different oxygen contents. Has been determined activation energy with value 7.53 meV at temperature range between 100 K and 250 K.